Selección en cruzas interraciales tropicales de maíz de México para adaptación a valles altos - Navas, Alejandro A.; Cervantes, Tarcicio (Agronomía Mesoamericana, 2016)
The response of the selection, and its adaptation at high plateaus, of five generations of tropical corn race crosses from Mexico, with a 0- 700 masl altitude range, was evaluated. An assay was planted at Montecillo, Mexico (locale with high plateaus) using four generations of 22 tropical interracial crosses, nine race progenitors and four local populations as controls. Besides of the grain yield per stalk, 15 characters were studied, some as yield components and others as of agronomic interest for its adaptation. The selection for high platea u adaptation with tropical corn inter-racial crosses was efective to increase grain yield per stalk, achiering an average response of 18% per selection cycle, in five cycles. Although with smaller increments, the number of ears per stalk, lenght, diameter and grain percentage of the ear, volume and weight of 100 seeds were modified. Ear and plant height showed undesirable agronomic responses, while days to tasselling, blooming coincidence and plant health improved with the selection. Six crosses in F8 were identified as matching the yield and other characters to the best local control Huamantla (conical race). According to the progenitors used in these crosses, it is deduced that the Tuxpeño race was the largest gene contributor for yield and Vandeño for adaptation genes, while Tepecintle showed a very poor gene contribution to the selection response.